Business Intelligence Dashboard Visualization Design for Project Performance Monitoring and Strategic Decision-Making Support - Erma Dearniwati; Antonius Darma Setiawan; Untung Suprihadi; USinka Wilyanti (Green Publisher Indonesia, 2026)
In today's competitive business era, fast, data-driven decision-making is critical to the success of organizations. Companies in the Event Contractor sector face challenges in managing complex data, as spreadsheet-based reporting systems are prone to input errors, outdated information, and manual calculation errors, leading to decreased profits and lost business opportunities. This research aims to design and implement a Business Intelligence Dashboard visualization for project performance monitoring to support strategic decision-making. The research applied a system design and development methodology that includes analysis of user needs and integration of data from various sources, using the Vercellis framework as a development approach. The designed dashboard displays key metrics such as project costs, profit and loss, and sales performance in an easy-to-understand visual format, allowing management to conduct evaluations faster and more accurately. The results show that the implementation of the Business Intelligence Dashboard reduces decision-making time from 7-14 working days to less than 7 working days, while increasing profit margins from 28% to 36.4% through better cost control and project evaluation. Integration of multiple data sources and interactive visualization features, including drill-down and filtering functions, allows for more in-depth data analysis and assessment. This research contributes to the development of an effective Business Intelligence Dashboard visualization design to improve project performance monitoring and strategic decision-making, as well as demonstrate how interactive visualizations can improve operational efficiency and business growth.